EKSPLORASI MODEL PEMBELAJARAN BERDIFERENSIASI DALAM MATEMATIKA - Moh. Supratman; I M. Ardana; I G. Putu Suharta; I W. Puja Astawa (FKIP Universitas Mataram, 2025)
This study is a systematic literature review (SLR) study that explores the application and effectiveness of differentiated learning models in mathematics learning. Differentiated learning involves tailoring content, processes, products, and learning environments to meet students' individual needs, with the goal of improving students' concept understanding, problem-solving skills, creativity, motivation, and engagement. This study identifies various differentiation approaches used in mathematics learning, such as subject-based learning, the use of educational technology, and flexibility in evaluation. The results show that differentiated learning is effective in improving learning outcomes, but its implementation is faced with challenges such as time constraints, teacher workload, variations in student abilities, and lack of training. The proposed solutions include increasing teacher training, more flexible time allocation, and developing varied and inclusive resources. The review also provides practical steps for the application of differentiated learning in mathematics classrooms, and recommends further research that integrates differentiated learning with open-ended problem-solving to improve mathematical creative thinking.